A Comprehensive Examination of 1.5 Tesla Magnetic Resonance Imaging (MRI) Through Overall Equipment Effectiveness Analysis : A Study Case on The Hospital Sector - Firdaus, Ade; Zulhamidi, Zulhamidi; Kristianti, Wike; Putri, Suci Imani; Restuasih, Sinta (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2025)
The research study focuses on hospitals with Magnetic Resonance Imaging (MRI) facilities which the population process for medical imaging equipment has experienced a higher average of values in every year which is data on the number of medical imaging devices in all Indonesian hospitals like Magnetic Resonance Imaging (MRI). Nowadays Magnetic Resonance Imaging (MRI) is a medical equipment really helpful to save patient for the diagnostic. High machine downtime and large number of lost time when trouble is still become a big problem for hospital when use medical equipment as a research object in this study. This research aim to analize OEE with Magnetic Resonance Imaging (MRI). The test parameters encompassed Performance, Availability, and Quality. Tolerance limits for these parameters were recommended by the World Class Overall Equipment Effectiveness. The study utilized a set to determine the entire workload and calculate the duration of MRI equipment usage. The findings revealed that, over a one-month observational period, only one measurement variable met the standards based on World Class OEE. The results shed light on the performance and efficiency of the MRI equipment in the context of diagnostic processes, providing valuable insights for further improvement and optimization. Keywords: Overall Equipment Effectiveness, Magnetic Resonance Imaging, Performance, Availability, and Quality